Effectiveness of a telemonitoring intensive strategy in early rheumatoid arthritis: comparison with the conventional management approach. Issue 1 (December 2016) - Salaffi, Fausto; Carotti, Marina; Ciapetti, Alessandro; Di Carlo, Marco; Gasparini, Stefania; Farah, Sonia; Gutierrez, Marwin
Abstract Background The advent of Internet and World Wide Web has created new perspectives toward interaction between patients and healthcare professionals. Telemonitoring patients with rheumatoid arthritis (RA) is an emerging concept to guide the collaborative management treatment and improve outcomes in patients. The objective of this study was to investigate whether an intensive treatment strategy, according to a telemonitoring protocol, is more effective than conventional management strategy in reaching remission and comprehensive disease control (CDC) after 1 year in early rheumatoid arthritis (ERA) patients. Methods Forty-four ERA patients were randomly allocated into two groups: the telemonitoring intensive strategy (TIS) group (group 1) or the conventional strategy (CS) group (group 2). Three patients refused to participate. In group 1 (n  = 21), a remote monitoring system of disease activity, in combination with protocolised treatment adjustments aiming for remission was applied. In group 2 (n  = 20), patients were treated according to daily clinical practice, with regular evaluation of disease activity, but without protocolised treatment adjustments. A telemedical care called "REmote TElemonitoring for MAnaging Rheumatologic Condition and HEaltcare programmes" (RETE-MARCHE), was developed to perform the remote monitoring. Results A higher percentage of patients in the TIS group achieved CDAI remission vs patients in the CS group (38.1 % vs 25 % at year 1, p <0.01). Time to achieve remission was significantly shorter in the group 1 than in the group 2, with a median of 20 weeks vs a median over 36-weeks (p <0.001). Concordantly, the patients in group 1 showed a greater improvement (p <0.001), compared with group 2 in terms of functional impairment (71.4 % vs 35 %) and radiological damage progression (23.8 % vs 10 %), resulting in a greater rate of CDC (19.4 % vs 5 %). Conclusions According to our results, an intensive treatment strategy by telemonitoring leads to more effective disease remission and more rapid CDC than treatment according to conventional management strategy in ERA. Trial registration Trial registration number:ISRCTN13142685 Date of registration: March, 17th 2016